Impact of a Proposed Training Course Using Cross-Training Some Physical and Physiological Variables of Players Have Hand-Ball (Field Study on National Hand-Ball Team Players) - seraiaia, Djamal (sports creativity, 2025)
The study was aimed at identifying the impact of cross-training on Some physical and physiological capabilities (muscular ability of men and arms, transitional speed, accuracy, respiratory league endurance, agility and lactic acid) of national handball team players, and the researcher used the experimental method on a sample of (10) hand ball players and study tools: Physical tests, physiological measurements, cross-training program, statistical methods used by SPSS V25, Among the most important results are: The intersecting training program has a statistically positive impact of 0.05 on physical capabilities (muscle capacity of men and arms, transitional speed, accuracy, respiratory and agility league endurance) of national handball team players, the proposed intersecting training program has improved physical capabilities (under study) The National Handball military Team (17.74% - 32.13%) has a statistically positive impact at 0.05 on the physiological (lactic acid) variables of the National military Handball Team (NFL), the proposed cross-training program has improved physiological variables (under study) Estimated at -15.19%